Peranan Masyarakat Sipil Dalam Pemberantasan Korupsi: Studi Kasus Indonesia Corruption Watch (ICW) Tahun 2014 - annisa rezayana; nur hidayat sardini; susilo utomo (Journal of Politic and Government Studies, 2016)
AbstractThe problem of corruption in Indonesia seems like an unseparated part of the government. Many different ways and efforts have been made by the government of Indonesia against corruption since the old order era, the new order era, even the reformation era and. One of many causes which predisposes to a weak eradication of corruption in the era of new order and the older order is the ‘top down’ method that used, where the eradication of corruption is can be done only if there is an instruction from superior (in this case the president). Different from the method of ‘bottom up’ where the eradication of corruption is done after there are any advisory from the citizen. This method is more appropriate with the democracy governance system, where the freedom of citizen to give an opinion and to contend is an important role to supervise the government. Indonesian Corruption Watch (ICW) is one of many organization which represents civil society, which also a pioneer of social movement on eradicating corruption. In 2012 the role of civil society is mostly needed in eradicating corruption, wherein the attempt to criminalizes KPK occured. In that time ICW with the coalition of anticorruption citizen have made an action #SaveKPK to rescue the institution. This research uses qualitative method with study case. The result of this research shows that there are three main roles played by ICW as a representation of civil society in fighting against corruption. First, is the role as a facility to amplifies the ‘Good Governance’ in society. Second, is the role as a link between the society and the government. And the Third is a role to support public campaign to urge the reformation of law, politics and bureaucracy that is conducive for the extermination against corruption. Key Words: Civil Society, ICW, Corruption.